Pengaruh Inflasi Dan Suku Bunga Terhadap Return Saham Dengan Profitabilitas Sebagai Variabel Moderasi Pada Perusahaan Indeks Lq 45 Di BEI Tahun 2019-2021 - Ardiansyah Japlani; Febiyanto; Paramita Citra Abadi (Universitas Muhammadiyah Metro, 2024)
The development of a free business world as it is today, it is no stranger to the public to make investments with the aim of obtaining greater returns than investing in the banking sector. Investment is now an open secret where all investors can easily access and channel their funds to companies they consider promising and capable of providing more value to what they have invested. the research used by researchers is descriptive with a quantitative approach which aims to find out whether inflation affects stock returns, to find out whether interest rates affect stock returns, to find out whether the profitability variable can moderate the relationship of inflation to stock returns, to find out whether the profitability variable can moderate the relationship between interest rates and stock returns. The sample used is a company that is active and consistent in the LQ 45 index during the 2019-2021 period. As well as data regarding the research variables to be examined are fully available in the company's financial reports published during the 2019-2021 period. Data analysis techniques using descriptive analysis, classic assumption test, hypothesis testing and moderating variable test. The result of this research is that inflation has a significant influence on stock returns at LQ 45 companies in 2019-2021. Interest rates have a significant influence on stock returns in LQ 45 companies in 2010-2021. profitability affects the relationship of inflation to stock returns in LQ 45 companies in 2019-2021. profitability affects the relationship between interest rates and stock returns in LQ 45 companies in 2019-2021.